Long‐term safety and efficacy of subcutaneous implantable cardioverter‐defibrillator compared with transvenous implantable cardioverter‐defibrillator in propensity score‐matched patients from Japan - Yuki Konno; Shingo Sasaki; Yuji Ishida; Yuichi Toyama; Kimitaka Nishizaki; Takahiko Kinjo; Taihei Itoh; Masaomi Kimura; Kazufumi Kato; Toshihiro Iwasaki; Hitoshi Umezaki; Shun Hirosawa; et al. (Journal of Arrhythmia)
Abstract Background Subcutaneous implantable cardioverter‐defibrillator (S‐ICD) has been reported to be non‐inferior to transvenous ICD (TV‐ICD) in terms of device‐related complications and inappropriate shock (IAS). We aimed to evaluate the long‐term clinical outcomes of S‐ICD compared with TV‐ICD in Japanese patients. Methods We studied 315 consecutive patients (TV‐ICD, 167; S‐ICD, 148) who underwent ICD implantation. A propensity score matching analysis was performed to select patient subgroups for comparison (104 patients in each group). Clinical outcomes, including appropriate and inappropriate ICD therapy, procedure‐ and lead‐related complications, and mortality, were compared between the two groups. Results During follow‐up (median, 1458 [interquartile range, 1353–1572] days), the cumulative incidence of appropriate shock therapy was 9.6% and 8.7% in the S‐ICD and TV‐ICD groups, respectively (p = 0.94). Although the S‐ICD group tended to have a higher IAS than the TV‐ICD group (5.8% vs. 1.9%), the difference was not significant (p = 0.19). Conversely, the cumulative incidence of procedural and lead‐related complications was significantly lower in the S‐ICD group (2.9% vs. 9.6%, p = 0.02). Notably, lead‐related complications were more common in the TV‐ICD group (p = 0.05). There was no difference in all‐cause mortality between the two groups (p = 0.75), and heart failure exacerbation was the most common cause of death in both groups. Conclusions In propensity score‐matched Japanese patients with S‐ICD, the cumulative incidence of appropriate shock and mortality was comparable to those with TV‐ICD. There was no significant difference in the rate of IAS. Notably, patients with S‐ICD had fewer lead‐related complications than those with TV‐ICD.